2015
DOI: 10.1111/1365-2435.12536
|View full text |Cite
|
Sign up to set email alerts
|

Multiple environmental drivers structure plant traits at the community level in a pyrogenic ecosystem

Abstract: Summary Trait‐based approaches offer a way to predict changes in community structure along environmental gradients using measurable properties of individuals. Promoted as being generalizable across systems, trait‐based approaches benefit from information about the environmental drivers of trait variation, how they interact and how they change with scale. However, for most diverse, natural communities, it is largely unknown whether the relationships between leaf‐level traits and interacting environmental driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 75 publications
(174 reference statements)
5
32
0
Order By: Relevance
“…These methods can still be somewhat limiting as focusing on the mean trait, even within subpopulations, neglects the effect of extreme values in the tails of the trait distributions, which may have a profound impact on community response to the environment (Bolnick et al, 2011). Ames, Anderson & Wright (2015) found that statistical inference regarding the environmental drivers of trait variation was greatly altered when using regional species means rather than locally measured trait values. There are several modelling approaches that are better suited for incorporating intraspecific variation into models of community dynamics and function.…”
Section: (2) How Does Significant Variability Within Species Affect Omentioning
confidence: 99%
“…These methods can still be somewhat limiting as focusing on the mean trait, even within subpopulations, neglects the effect of extreme values in the tails of the trait distributions, which may have a profound impact on community response to the environment (Bolnick et al, 2011). Ames, Anderson & Wright (2015) found that statistical inference regarding the environmental drivers of trait variation was greatly altered when using regional species means rather than locally measured trait values. There are several modelling approaches that are better suited for incorporating intraspecific variation into models of community dynamics and function.…”
Section: (2) How Does Significant Variability Within Species Affect Omentioning
confidence: 99%
“…Fort Bragg is composed of burn parcels (hereafter "sites") with independent burn histories. Permanent vegetation sampling transects spanning the topographic gradient have been maintained in 32 sites since 2011; the burn regime in the majority of these sites has been experimentally altered, with a subset of sites being maintained in 3-year burn intervals (Ames et al, 2015).…”
Section: Study Site and Fire Characteristicsmentioning
confidence: 99%
“…Thus, we were left with five study sites: B1, B2, and B3 experienced burns in 2014; C1 and C2 were control sites that remained unburned. Our study sites, renamed here for clarity, correspond to sites 3 and 11 (wildfire site), 15b (B1-3), and 9 and 32 (C1 and C2) described in Ames et al (2015). At each site, we established a 1 m 2 sampling area approximately 5 m upslope of the ecotone.…”
Section: Study Site and Fire Characteristicsmentioning
confidence: 99%
“…We conducted a trait analysis of 11 plant traits measured on 107 species (63 685 measurements total) from a longleaf pine forest understory in North Carolina, USA (see [24] for trait collection methods and site description). We included a variety of common plant traits, such as SLA (cm 3 g 21 ),…”
Section: Is Variability In Traits Correlated Across Species?mentioning
confidence: 99%